Hypertension in children: review of current challenges and state of knowledge - Bochenek, Michał; Filip, Kinga; Jakubowski, Wojciech (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Hypertension in children is an emerging global health concern, with a growing prevalence influenced by rising obesity rates and socioeconomic disparities. This review examines the multifactorial nature of pediatric hypertension, distinguishes between primary and secondary forms, and highlights pathophysiological mechanisms, including arterial remodeling, sympathetic overactivity, and metabolic dysfunction. Family socioeconomic status, including parental income and education level, is closely linked to hypertension risk. Obesity plays a central role by promoting sympathetic activation, renin-angiotensin-aldosterone system (RAAS) stimulation, and insulin resistance. Despite clear diagnostic guidelines, hypertension in children remains underdiagnosed because of its asymptomatic nature and diagnostic challenges. Early detection is critical, as the condition is associated with target organ damage and increased cardiovascular risk. Effective management involves lifestyle modifications, dietary changes such as the dietary approaches to stop hypertension (DASH) diet, physical activity, and, when necessary, pharmacotherapy. Public health strategies, clinician education, and school-based screening are essential for prevention and early intervention to curb this growing pediatric health crisis.